The Formation of the Image of the Enemy in Lithuanian Media Outlets: The Polish Question - Makarova, Viktorija (Respectus Philologicus, 2013)
This article analyzes the opposition of Polish and Lithuanian identities as presented in Lithuanian media outlets. It is assumed that an information war is being waged against the Polish cultural minority and that the instigators of this war are achieving their goal, i.e., being Polish bears a negative association in the public consciousness, which also construes Poles as enemies. The article investigates the means by which this negative opinion about the Polish nationality in Lithuania is formed. The conclusions are based on an analysis of four articles and more than 40 headlines published in 2012–2013, and show that the editors of Lithuanian media outlets regularly present news about events in Poland and/or Poles themselves by choosing information that casts aspersions on the country and its inhabitants. The readers of the Lithuanian media are constantly fed the idea that Poles are characteristically nationalistic. Indeed, the media frequently discuss the danger to Lithuanians posed by Poles in Lithuania. This phenomenon can be explained by the Copenhagen School’s Theory of Securitization: a problem that is technical in nature is given the status of an existential threat. Texts often convey the antithesis Poles—Lithuania, in which the first element is given only negative features and the second only positive. Attention is also drawn to the distorted usage of the word “discrimination”: in Lithuanian media outlets it is applied when discussing the stronger member of the conflict.
Keywords: Enemy; Image; Poles; Lithuanians; Polonization; Lithuanian Identity; Political Instrument; Media